An improved CVM entropy functional for binary fcc alloys - Jindal V.; Nageswara Sarma B.; Lele S. (My University, 2025)
We explore the possibility of modifying the multiplicity of the basic clusters in the entropy functional used in the cluster variation method so that the truncation errors arising due to finite size of the basic clusters may be corrected. The numerical values of the multiplicity of the basic clusters are found by requiring the modified CVM entropy functional in the tetrahedron-octahedron approximation for the face-centered cubic structure to yield the nearly exact critical temperatures for ordering and phase separating systems. This modification correctly reproduces the triple point in a prototypical fcc ordering system, using the same first neighbor pair interaction energy parameter for all the ordered (L10 and L12) and disordered (A1) phases, without increasing the computational burden and thereby making a long standing problem tractable. The modification also improves the agreement between the values of thermodynamic quantities (for ordered and disordered phases at arbitrary temperatures and compositions) obtained from CVM and Monte Carlo simulations. © 2013 Elsevier Ltd. All rights reserved.